2005
DOI: 10.1079/phn2004700
|View full text |Cite
|
Sign up to set email alerts
|

The temporal pattern of the contribution of fat to energy and of food groups to fat at various eating locations: implications for developing food-based dietary guidelines

Abstract: Objectives: To examine the temporal pattern of the number of eating occasions that occurred at home, at work and outside the home, and to examine the contribution of fat to energy and the contribution of 26 food groups to fat at home and outside the home. Design and setting: Food intake data were collected using a 7-day food diary from a random sample of 18 -64-year-old adults from the Republic of Ireland (n ¼ 958). Respondents recorded the day, time and location of every eating occasion. Results: The number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 22 publications
1
29
1
Order By: Relevance
“…[25][26][27][28][29][30][31] The reported increase in energy intake that occurs over the weekend coupled with the reduction in physical activity reported on a Sunday in the overweight participants suggests that weekends are a time of positive energy balance in this at-risk group. It would be useful for future studies to compare daily energy intakes with daily step counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29][30][31] The reported increase in energy intake that occurs over the weekend coupled with the reduction in physical activity reported on a Sunday in the overweight participants suggests that weekends are a time of positive energy balance in this at-risk group. It would be useful for future studies to compare daily energy intakes with daily step counts.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the overweight participants accumulating, on average, the recommended 10 000 steps/day 32 on Monday through to Saturday, it could be speculated that owing to a potential positive energy balance, as suggested by research investigating patterns in energy intake over different days of the week, [25][26][27][28][29][30][31] coupled with the decrease in activity observed in this group on a Sunday, accumulating 10 000 steps/day on 6 days per week is not sufficient to prevent unhealthy fat accretion.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, eating out-of-home is associated with increased EI and fat intakes (18)(19)(20) , and is an independent risk factor for obesity (21)(22)(23) . This is of particular concern given the increased frequency of out-of-home eating over time.…”
mentioning
confidence: 99%
“…Results from recent studies have identified how socio-environmental and personal factors impacted eating behavior within eating situations. For example, structure of the day, regularity and habit were important influences on meal frequency, location, and intake by adults (15)(16)(17). Social setting as an attribute of an eating occasion was described as including the dimension of "presence of others" and social processes such as celebration or bonding (18).…”
Section: Introductionmentioning
confidence: 99%